Green School and Its Implementation in Islamic Educational Institutions in Indonesia - Mahyani, Aang; Ruswandi, Agus (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
Climate change regarding global warming threatens human life on earth, so there needs to be solutions from various parties to reduce the negative effects of climate change. Implementing these principles in Islamic educational institutions in Indonesia still needs to improve understanding, policies, and implementation in the field. Therefore, this study aims to analyse the implementation of Green Schools in Islamic educational institutions in Indonesia, identifying factors that support and hinder its implementation. The research method used is a case study with a qualitative approach—data collection techniques using document analysis from research results published in national and international journals. Data analysis is done through data condensation, data display, and verification. The green school program is a program that must be implemented in educational institutions. Green schools and green buildings can improve teacher performance and academic achievement. Various Islamic educational institutions have carried out green school programs; some have received Adiwiyata awards from the Indonesian Government. However, Islamic education institutions still need to implement green schools properly. Islamic educational institutions should consistently implement green school programs in their respective institutions to reduce climate change's negative effects. Perubahan iklim dan pemanasan global mengancam kehidupan manusia, sehingga diperlukan solusi dari berbagai pihak untuk mengurangi dampak negatifnya. Salah satu solusi adalah program green school di lembaga pendidikan, termasuk di lembaga pendidikan Islam di Indonesia. Namun, implementasi program ini masih menghadapi tantangan, terutama terkait pemahaman, kebijakan, dan pelaksanaan di lapangan. Penelitian ini bertujuan untuk menganalisis implementasi green school di lembaga pendidikan Islam, serta mengidentifikasi faktor pendukung dan penghambatnya. Metode yang digunakan adalah studi kasus kualitatif dengan teknik analisis dokumen dari jurnal nasional dan internasional. Program green school memiliki manfaat, seperti meningkatkan kinerja guru dan prestasi akademik siswa. Walau beberapa lembaga telah meraih penghargaan Adiwiyata, konsistensi penerapan di lembaga pendidikan Islam perlu ditingkatkan untuk mengurangi dampak perubahan iklim.